2014
DOI: 10.1016/j.jacc.2014.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Cardiac Troponin T, But Not Cardiac Troponin I, in Patients With Neuromuscular Diseases

Abstract: Patients with a wide spectrum of neuromuscular diseases commonly have persistent elevation of cTnT and CK-MB in the absence of clinical and cTnI evidence of myocardial injury. Re-expressed cTnT in diseased skeletal muscle appears to be the source of the elevated cTnT detected in the circulation of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
104
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 52 publications
3
104
0
2
Order By: Relevance
“…Interestingly, the up-regulation of troponins is a marker of heart failure (66). The differential expression of TnT relative to TnI in heart disease (67) supports the idea that differences in their expression are related to CM function. Further study is needed to understand how stiffness and shape regulate the expression of sarcomere proteins.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, the up-regulation of troponins is a marker of heart failure (66). The differential expression of TnT relative to TnI in heart disease (67) supports the idea that differences in their expression are related to CM function. Further study is needed to understand how stiffness and shape regulate the expression of sarcomere proteins.…”
Section: Discussionmentioning
confidence: 83%
“…Whereas injury to myocardium causes the simultaneous release of both cTnI and cTnT into the circulation, denervation and chronic injury of skeletal muscle may induce expression and release of cTnT, but not cTnI, from the skeletal muscle. Therefore, elevated circulating cTnT, but not cTnI, has been found in patients with various neuromuscular diseases and in healthy elderly patients without clinical cardiovascular disease 7, 9…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Recently, an elevation of plasma cTnT in the absence of cardiac troponin I (cTnI) in several neuromuscular diseases has been shown. 9 It has been suggested that diseased skeletal muscle tissue is an alternative source for elevated cTnT levels in certain neuromuscular conditions and dialysis patients.…”
mentioning
confidence: 99%